Imaginaţie, memorie, (re)lectură, în opera lui Matei Călinescu - Raluca Dună (Revista de Istorie și Teorie Literară)
This article explores the very diverse works of the Romanian critic, poet and novelist Matei Călinescu, focusing on the importance of the author’s imagination, conceived as a major principle in his critical or artistic writing. The autobiographical project that encompasses his whole work is governed by this creative principle, whose importance seems to have been recognized first by the great Romanian exile Mircea Eliade, who is seen in this article as a kind of a paternal and mythical figure for the Romanian exile. The return to the maternal language and to fiction is perceived, in this sense, as the return to a Romanian paradoxical identity. The article describes the relationship between critical interpretation, personal memory and bookish imagination, analyzing a few fragments from the Romanian edition of the volume (Re)reading.